Improving Students Vocabulary Mastery Using Flashcard at The KAI - Kholisoh Nursaadah; Yon A E (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This study discusses the improvement of students' English vocabulary by using flashcards. This research aims of the paper are: (1) Can flashcards improve students' vocabulary, (2) What is the students' vocabulary achievement before and after using flashcards. The subjects of this study were students in Brainy English at The KAI, where a total of 30 students were from classes D1 to D4. This research was conducted in the academic year 2022/2023. The model of Classroom Action Research (CAR) is stated by Kemmis and Mc Taggart (in Burns, 1993:32) who state that the model of Classroom Action Research is consist of four steps. They are namely: planning, acting, observing, and reflecting. Based on this study, it was stated that there was an increase in students' vocabulary after learning using flash cards. The average value of student achievement in cycle 1 was 65.5, and the average value of student achievement increased to 79.7 in cycle 2. Therefore, the author can conclude that the use of flashcards is the most appropriate medium to attract students' interest and make the classroom atmosphere fun and can improve student learning outcomes vocabulary. The author hopes that this thesis can be used as an additional reference, namely: will be the next researcher with a different discussion who can revise the development of this flashcard.